2020
DOI: 10.1017/s1366728920000486
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in bilingual experience modulate executive control network and performance: behavioral and structural neuroimaging evidence

Abstract: Dual/multiple language use has been shown to affect cognition and its neural substrate, although the replicability of such findings varies, partially due to neglecting the role of interindividual variability in bilingual experience. To address this, we operationalized the main bilingual experience factors as continuous variables, investigating their effects on executive control performance and neural substrate deploying a Flanker task and structural magnetic resonance imaging. First, higher L2 proficiency pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 74 publications
2
15
0
Order By: Relevance
“…For example, increasing length of immersion, L2 exposure, and L2 proficiency has been shown to modulate L1 ERP responses among bilingual "L1 attriters" themselves (e.g., Kasparian and Steinhauer, 2017a;Miller and Rothman, 2020). This is in line with recent findings demonstrating that variations in the aforementioned bilingual experiential factors have a discernible impact on the linguistic neurobiology, neurocognition, and behavior of the bilinguals (e.g., Gullifer et al, 2018;DeLuca et al, 2019;Gallo et al, 2021;Sulpizio et al, 2020).…”
Section: Who Is the L1 Attriter-a Bilingual By Another Name?supporting
confidence: 82%
“…For example, increasing length of immersion, L2 exposure, and L2 proficiency has been shown to modulate L1 ERP responses among bilingual "L1 attriters" themselves (e.g., Kasparian and Steinhauer, 2017a;Miller and Rothman, 2020). This is in line with recent findings demonstrating that variations in the aforementioned bilingual experiential factors have a discernible impact on the linguistic neurobiology, neurocognition, and behavior of the bilinguals (e.g., Gullifer et al, 2018;DeLuca et al, 2019;Gallo et al, 2021;Sulpizio et al, 2020).…”
Section: Who Is the L1 Attriter-a Bilingual By Another Name?supporting
confidence: 82%
“…Such variability has been recently ascribed to the tendency of dichotomizing the spectrum of bilingual experience, i.e., favoring group comparisons between "bilinguals" and "monolinguals" over a detailed, continuous assessment of the individual bilingual experience (e.g., Luk and Bialystok, 2013;Surrain and Luk, 2019). To overcome this issue, in line with recent investigations (e.g., Hervais-Adelman et al, 2018;DeLuca et al, 2019;Gallo et al, 2021), here we operationalized bilingual experience continuously, for the first time to our knowledge in an investigation on senior individuals.…”
Section: Introductionmentioning
confidence: 84%
“…The study reported here investigated, for the first time to our knowledge, the effects of bilingualism on executive functioning during senescence operationalizing the bilingual experience as a continuous rather than a categorical variable. This approach, while in line with the general recent trend in bilingualism research (e.g., Hervais-Adelman et al, 2018;DeLuca et al, 2019;Del Maschio et al, 2020;Gallo et al, 2021), was yet to be applied to studies on senior individuals. A continuous assessment of the bilingual experience allows to draw a more detailed, individualized linguistic profile for a life experience that is intrinsically different for each individual, thus contributing to overcoming issues related with inconsistencies in methodological designs and results, which have been plaguing bilingualism research in recent years (Luk and Bialystok, 2013;Mishra, 2015;Surrain and Luk, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, existing research has reported the beneficial effects of bilingualism beyond the language system-by showing positive bilingual effects on the general cognitive abilities, including memory (Soliman 2014;Hernández et al 2012), attention (see Bialystok 2015, for review), and executive function (Abutalebi et al 2013;Antoniou et al 2016;Morales et al 2015)-to the general cognitive systems involved in parallel monitoring, inhibition, and control of linguistic processing in two or more languages. Importantly, this general effect is accompanied by neuroanatomical structural changes such that higher L2 proficiency levels are associated with more efficient functional connectivity in the brain areas supporting executive control (Sulpizio et al 2020;Gallo et al 2020Gallo et al , 2021. Although still controversial and presently a subject of fierce debate (see for instance Paap and Greenberg 2013), these facilitatory "bilingual effects" are an example of how an increase in L2 proficiency may affect both linguistic and general cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%